THE USE OF THE PROPELLER FLAP FOR COVERING SKIN DEFECT AFTER AXILLARY LYMPHADENECTOMY FOR BREAST CANCER - I. V. Reshetov; V. A. Khiyaeva; K. G. Kudrin; A. S. Fatyanova (Сибирский онкологический журнал, 2021)
The purpose of the study was to assess the feasibility of using the propeller flap to cover a large axillary fossa defect following lymph node dissection in breast cancer patients.Material and Methods. One hundred breast cancer patients underwent surgery. Out of them, 64 underwent Madden modified radical mastectomy and 36 radical breast resection using a propeller muscle flap. Out of 100 patients, 61 were followed up (50 after mastectomy and 11 after radical resection using a propeller flap). Fifteen patients were randomly selected for examination of the flap using ultrasound (2 patients after radical resection, 13patients after radical mastectomy). The follow-up time was from 3 to 6 months. We studied the following: bleeding in the postoperative period, hematoma, duration of lymphorrhea, duration of hospitalization, ultrasound findings, hand function, size of the upper limb, and physical activity.Results. No statistically significant differences in the number of complications related to the surgery extent were found. Here was no bleeding. Small hematoma was observed in one patient who underwent breast resection. Forty-three (70.49 %) patients did not have lymphorrhea after drainage removal. Lymphorrhea was observed for a month in 9 (14.75 %) patients, for 1–2 months in 4 (6.56 %) patients, and for 3 months or more in 5 (8.2 %) patients – 3 months or more. Twelve (19.67 %) patients developed lymphoedema of the arm. Hospitalization period was 7 bed-days in 90.0 % of cases. The flap viability reached 100.0 %. In 54 (88.53 %) of 61 patients, the active function of the arm recovered. Thirty-eight (62 %) patients had ECOG 1 status 3 years after surgery.Conclusion. The flap made it possible to solve the local problems of covering the axillary neurovascular bundle during lymphadenectomy for breast cancer and eliminating a large axillary fossa defect. The results obtained demonstrated high engraftment rates with a small number of complications, regardless of the surgery extent.